2022
DOI: 10.1038/s41467-022-34150-7
|View full text |Cite
|
Sign up to set email alerts
|

A fungal NRPS-PKS enzyme catalyses the formation of the flavonoid naringenin

Abstract: Biosynthesis of the flavonoid naringenin in plants and bacteria is commonly catalysed by a type III polyketide synthase (PKS) using one p-coumaroyl-CoA and three malonyl-CoA molecules as substrates. Here, we report a fungal non-ribosomal peptide synthetase -polyketide synthase (NRPS-PKS) hybrid FnsA for the naringenin formation. Feeding experiments with isotope-labelled precursors demonstrate that FnsA accepts not only p-coumaric acid (p-CA), but also p-hydroxybenzoic acid (p-HBA) as starter units, with three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“…A similar chimeric AT-PKS, P168DRAFT_323099 (CfvA in this study), was proposed to be involved in the biosynthesis of chlorflavonin, which is the first example of a fungal flavonoid, the producer of which was confirmed to be Aspergillus candidus (Figure B) . More recently, Zhang et al demonstrated that this type of AT-PKS catalyzes the formation of 1 and naringenin ( 2 ) . Herein, we report the functional characterization of DiapA, showing that this enzyme also catalyzes the formation of 1 and that its TE domain is responsible for the characteristic Claisen-type cyclization.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…A similar chimeric AT-PKS, P168DRAFT_323099 (CfvA in this study), was proposed to be involved in the biosynthesis of chlorflavonin, which is the first example of a fungal flavonoid, the producer of which was confirmed to be Aspergillus candidus (Figure B) . More recently, Zhang et al demonstrated that this type of AT-PKS catalyzes the formation of 1 and naringenin ( 2 ) . Herein, we report the functional characterization of DiapA, showing that this enzyme also catalyzes the formation of 1 and that its TE domain is responsible for the characteristic Claisen-type cyclization.…”
supporting
confidence: 62%
“…Heterologous expression in A. oryzae , isolation and structural analysis of the metabolites, and structural prediction of the terminal TE domain and molecular docking analysis clearly indicated that DiapA is a dedicated chalcone synthase distinct from plant type III PKS. The previous study also identified FnsA, a DiapA homologue, synthesized 1 and 2 . However, it remains unclear whether the cyclization of 1 to 2 is an enzymatic process or not.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The TAS1 PKS part has a KS domain alone with a unique sequence. After discovery of TAS1, some fungal NRPS-PKS enzymes (SwnK (A-PCP-KS-AT-KR-ACP-R), , HispS20 (A-PCP-KS-AT-ACP), AnATPKS21 (A-PCP-KS-AT-ACP), HppS (A-PCP-KS-AT-ACP), AcdB (A-PCP-KS-AT-KR 0 -ACP-R 0 ), and FnsA (A-PCP-KS-AT-DH-KR-ACP-TE)) have been reported. All these enzymes have AT and ACP domains and lack C domain.…”
Section: Introductionmentioning
confidence: 99%